The early onset of type 1 autoimmune hepatitis has a strong genetic influence: role of HLA and KIR genes - Podhorzer, Ariel (2016)
We have previously reported a strong association between HLA-DRB1*1301 and type 1 pediatric autoimmune hepatitis (PAH) andbetween HLA-DR*0405 and adult autoimmune hepatitis (AAH). Because human killer cell immunoglobulin-like receptors are knownto be associated with susceptibility to autoimmune diseases, we investigated the frequencies of HLA-A, B, C, DRB1 and KIR genes in144 type 1 PAH and 86 AAH patients, which were compared with 273 healthy controls. We demonstrated in PAH the increasedfrequency of the functional form of KIR2DS4-Full Length (KIR2DS4-FL), which in combination with HLA-DRB1*1301 revealed astrong synergistic effect (odds ratio = 36.5). PAH-KIR2DS4-FL+ subjects have shown an increased frequency of their putative HLAC*02, 04 and 06 ligands. KIR analysis of PAH also revealed a decreased frequency of KIR2DL2 gene and its ligand. In contrast, AAHcases have shown a weaker increased frequency of KIR2DS4-FL, a lack of synergistic effect with HLA class II antigens and amoderate association with HLA-DRB1*0405. Of note, we demonstrated that liver T cells have a unique pattern of KIR expression.These results show a KIR gene involved in autoimmune hepatitis and suggest a stronger genetic influence for the early onset type Iautoimmune hepatitis.